2021
DOI: 10.2196/20175
|View full text |Cite
|
Sign up to set email alerts
|

Medical Food Assessment Using a Smartphone App With Continuous Glucose Monitoring Sensors: Proof-of-Concept Study

Abstract: Background Novel wearable biosensors, ubiquitous smartphone ownership, and telemedicine are converging to enable new paradigms of clinical research. A new generation of continuous glucose monitoring (CGM) devices provides access to clinical-grade measurement of interstitial glucose levels. Adoption of these sensors has become widespread for the management of type 1 diabetes and is accelerating in type 2 diabetes. In parallel, individuals are adopting health-related smartphone-based apps to monitor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Participants expressed great satisfaction with the sensors, product, and app, and no negative incidents were noted. The need for larger research in the future is indicated by the considerable alterations in postprandial glucose response that were found in real-world settings, even though statistical Applications of Cutting-Edge Biosensors in Healthcare and Biomedical Research DOI: http://dx.doi.org/10.5772/intechopen.112693 significance could not be reached [41]. For noninvasive interstitial fluid (ISF) extraction and real-time glucose testing, a screen-printed iontophoretic biosensing system has been created.…”
Section: Wearable Biosensorsmentioning
confidence: 99%
“…Participants expressed great satisfaction with the sensors, product, and app, and no negative incidents were noted. The need for larger research in the future is indicated by the considerable alterations in postprandial glucose response that were found in real-world settings, even though statistical Applications of Cutting-Edge Biosensors in Healthcare and Biomedical Research DOI: http://dx.doi.org/10.5772/intechopen.112693 significance could not be reached [41]. For noninvasive interstitial fluid (ISF) extraction and real-time glucose testing, a screen-printed iontophoretic biosensing system has been created.…”
Section: Wearable Biosensorsmentioning
confidence: 99%
“…It is well described that blood glucose levels change after a meal and that postprandial glucose responses (PPGR) depend on the macronutrients consumed, the time of day, and the individuals underlying beta-cell function. 14,15 Postprandial glucose responses are increasingly considered a major determinant of glycemic control, yet methods for predicting PPGR to food remain elusive and of limited efficacy. 16 CGMs can be utilized to evaluate the frequency with which individuals demonstrate elevations in postprandial glucose, the types of patterns, and how patterns vary between individuals given an identical nutrient challenge.…”
Section: Effects Of Diet On Glycemia Learned From Using Cgm Datamentioning
confidence: 99%